Ograniczenia aksjologiczne prawniczych wnioskowań instrumentalnych - Lewandowski, Andrzej (Wydział Prawa i Administracji UAM, 1984)
The author advocates in the article that a system of values ascribed to a rational legislator must be accounted for in applying rules of legal reasoning grounded on instrumental relation between acts indicated by norms. It is a complex problem as a global study of situation has to be considered and specific estimation of its aspects does not seem to be sufficient. The difficulties are also indicated in refering to casual nexus between states of things determined by norms for execution according to the rule of instrumental order or the rule of instrumental prohibition. There is a problem among others, how far the assumed causality has to be accounted for. One often recalls to enthymematic premises upon describing necessary conditions to realize a state of things indicated by a norm. These should be revealed if a reconstruction of a system of legal norms on the grounds of legal texts has to be performed in a clear and justified manner.
Axiological limitations of legal instrumental reasoning